Explaining the perception of students and professors regarding the clinical education challenges and strategies of the operation room - Somayeh Akbari Farmad; Marzieh Khosravi; Sadegh Abaei Hasani; Sarvin Bosak (Journal of Education and Health Promotion)
BACKGROUND: Clinical education is an essential part of medical science education in the operating room, and considering its high importance, it is necessary to identify challenges in this regard. The study aims to explain the perception of students and professors regarding the challenges and strategies for improving education in the operating room. The context of this study was the Khomein School of Medical Sciences. MATERIAL AND METHODS: This was a qualitative study and conventional content analysis research that was conducted in 2023, using semi-structured interviews. The study population included professors and students of the operating room of the Khomein School of Medical Sciences that were selected using the snowball sampling method. The data reached saturation with five interviews with professors and seven interviews with students. This study used Graneheim and Lundman’s method for data analysis. RESULT: The most important educational challenges in the operating room from the students’ perspectives included the need to improve educational and welfare spaces, the need for effective teacher-student interaction, the need to improve educational-hospital facilities and equipment, and the need for effective student-physician-operating room staff atmosphere. The most important challenges from the professors’ perspectives included correct professional and ethical principles in dealing with students and effective psychological and educational support by the professor. The most important strategies from the students’ perspectives included effective clinical interactions, supportive clinical professors, and clarification of educational duties and expectations, and from the professors’ perspectives included improving the clinical environment, a competent clinical professor, and the need for effective educational information. CONCLUSION: This study can increase the awareness of clinical professors and educational managers of operating room majors about clinical education challenges in this field and strategies for solving them. Finally, such actions can help to create a more effective clinical environment.